Analysis of Feasibility and Practice of Science Literation Based Practicum Module - Marjanah Marjanah; Nurmasytah Nurmasytah; Nursamsu Nursamsu; Raja Novi Ariska (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this study was to determine the feasibility and practicality test of the science literacy-based practicum module for science learning at SMA Muhammadiyah Kota Langsa. The research method used is education development (Education Research and Development) to determine the quality or feasibility of the module as a practical guide. This practicum module is analyzed the feasibility test by material and media experts consisting of biology and physics education lecturers, while the practicality test uses a questionnaire distributed by science subject teachers. The results showed that the IPA practicum module products analyzed consisted of four categories with a percentage value of 54.99% content feasibility, 60.00% language value, 48.33% presentation value and 66.66% graphics value. Furthermore, a practicality test was carried out which consisted of three aspects, namely the content aspect of 82.85%, the process of the value of 77.14% and the context of the value of 54.28. Based on the values obtained, the science practicum module is feasible and practical to use as a practicum guide.